Identification of novel immunomodulators in the Vaccinia virus genome - Landsberger, Mariann (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2016)
A crucial early step for the initiation of an effective anti-viral response after sensing the presence of viruses is the activation of the transcription factors nuclear factor kappa-B (NFkB) and interferon regulatory factors (IRFs) by pattern recognition receptors (PRR). These transcription factors drive the expression of proinflammatory cytokines and type I interferons. Large double-stranded DNA poxviruses, such as Vaccinia virus (VACV), have evolved numerous strategies to evade these host signalling systems and elucidation of such strategies has identified key mechanisms of innate immunity. The aim of this project is to discover novel intracellular VACV immunomodulators and characterise the role of their host targets in innate immunity.
Keywords: Biochemistry & Immunology, Ph.D.; PhD Trinity College Dublin, 2016